Cellulose nanocrystals incorporated with hydroxypropyl methylcellulose as biocomposite scaffolds for bone tissue engineering - Zulkifli, Farah Hanani (2019)
In this present work, a porous three-dimensional (3D) scaffold of HPMC/PVA and HPMC/PVA/CNC were successfully fabricated by freeze-drying technique. HPMC (5 wt%) and PVA (15 wt%) were dissolved and blended at a ratio of 50:50 and incorporated with CNC (1, 3, 5 and 7 wt%) as nanofiller to obtain a highly porous scaffolds. The morphology, mechanical and thermal properties of scaffolds were characterized by SEM, ATR-FTIR, and TGA. Meanwhile, cytotoxicity studies on both porous scaffold biomaterials were carried out by utilizing human fetal osteoblast (hFOB) cells using MTT assays and DAPI staining. Incorporated HPMC/PVA with CNC were exhibited superior functionality which resulted in decreasing average pore size and there were slightly changes in the chemical structure as determined by FTIR spectra. Thermal studies revealed that the melting temperatures of HPMC/PVA/CNC scaffold were slightly shifted to a higher value. It was observed that the hFOB cells were able to attach and spread on both scaffolds and supported the cell adhesion and proliferation. Due to its biocompatible and biodegradable properties, these newly developed highly porous scaffolds may provide a promising alternative scaffolding matrix for bone tissue engineering regeneration.